System error: hyperadaptation and failure in David Foster Wallace's "Good old neon" - Sánchez Usanos, David (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper is a close reading of David Foster Wallace’s Good old neon. We connect this short story with other Wallace’s works and with other documents of culture in order to think about our present time, about postmodernity and its contradictions. We analyze the possible ties between social success and personal failure, the paradoxes of reason and calculus, the link between competitiveness and emotional blockage and the commodification of experience. In addition to that we emphasize the literary and rethoric devices employed by David Foster Wallace with the purpose of represent and confront a diagnosis that was also his own.
Keywords: David Foster Wallace; postmodernity; fraud; hyperadaptation; failure; commodification of experience; emotional blockage; manipulation; metafiction